2000
DOI: 10.1016/s0925-4773(00)00365-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of the extracellular matrix during neural crest cell migration

Abstract: Once specified to become neural crest (NC), cells occupying the dorsal portion of the neural tube disrupt their cadherin-mediated cell-cell contacts, acquire motile properties, and embark upon an extensive migration through the embryo to reach their ultimate phenotype-specific sites. The understanding of how this movement is regulated is still rather fragmentary due to the complexity of the cellular and molecular interactions involved. An additional intricate aspect of the regulation of NC cell movement is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(173 citation statements)
references
References 94 publications
9
157
0
5
Order By: Relevance
“…Cryofractured specimens, which were prepared by removing separating the epidermis from the dermis to further analyze the underside of the epidermal tissue, were examined by SEM to confirm both the histological and histochemical data in platyfish-swordtail hybrid skin (Figure 4A-4C). They revealed that these neural crest/ premelanoblast cells exhibited their previously described characteristic morphology in Xiphophorus fish embryos [14] and other vertebrate embryos [27]. Thus they were pleomorphic with different elongated, spheroidal, spindle-like, flattened or irregular morphologies, and had intensive cell-ECM fibril contacts ( Figure 4A and 4B), as previously described in swordtail/platyfish [14].…”
Section: Generation Of Xiphophorus Hybrid Fishsupporting
confidence: 77%
“…Cryofractured specimens, which were prepared by removing separating the epidermis from the dermis to further analyze the underside of the epidermal tissue, were examined by SEM to confirm both the histological and histochemical data in platyfish-swordtail hybrid skin (Figure 4A-4C). They revealed that these neural crest/ premelanoblast cells exhibited their previously described characteristic morphology in Xiphophorus fish embryos [14] and other vertebrate embryos [27]. Thus they were pleomorphic with different elongated, spheroidal, spindle-like, flattened or irregular morphologies, and had intensive cell-ECM fibril contacts ( Figure 4A and 4B), as previously described in swordtail/platyfish [14].…”
Section: Generation Of Xiphophorus Hybrid Fishsupporting
confidence: 77%
“…CSPG GAG chains have been implicated in a variety of barrier-forming phenomena, including cell division (Mizuguchi et al, 2003), neural cell migration (Kubota et al, 1999;Perissinotto et al, 2000;Perris and Perissinotto, 2000), and inhibition of axon regeneration . cABC is effective at removal of GAG chains at the lesion site in vivo (McKeon et al, 1995;Moon et al, 2001;Bradbury et al, 2002), distal to the lesion site, when combined with a peripheral nerve graft (Houle et al, 2006), as well as in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A number of molecules are known to participate in neural crest delamination and migration, such as cadherins, Rho GTPases, Noggin and several extracellular matrix molecules (Borchers et al, 2001;Bronner-Fraser et al, 1992;Henderson et al, 2000;Hoffmann and Balling, 1995;Kimura et al, 1995;Liu and Jessell, 1998;Nakagawa and Takeichi, 1995;Nakagawa and Takeichi, 1998;Perris and Perissinotto, 2000;Pla et al, 2001;Sela-Donenfeld and Kalcheim, 1999;Sela-Donenfeld and Kalcheim, 2000;Takeichi et al, 2000;Vallin et al, 1998; Van de Putte et al, 2003;Yagi and Takeichi, 2000). However, the mechanisms by which extracellular signals are integrated with cell adhesion and cytoskeletal modification to orchestrate the cell movements underlying delamination and movement of the neural crest are still unclear.…”
Section: Introductionmentioning
confidence: 99%